Superior mesenteric artery syndrome - Aravindan Chandrasekaran (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2016)
Superior mesenteric artery syndrome is a very uncommon disorder in which acute angulation of superior mesenteric artery (SMA) at its origin from aorta results in compression of the third part of the duodenum leading to partial or complete obstruction of the duodenum. Other terminologies for this condition are Cast syndrome, Wilkie syndrome, arteriomesenteric duodenal obstruction, and chronic duodenal ileus.1 The disease is extremely rare in the pediatric population. Here we report a case of SMA syndrome in an 11 year old boy who was admitted with hepatitis, subsequently developed primary peritonitis and during his admission at the hospital he developed SMA syndrome. The case is being reported for its extreme rarity, to highlight the role of imaging in establishing the diagnosis and to review the literature in the subject.